Coding Clinical Information: Analysis of Clinicians Using Computerized Coding - Hohnloser, J. H.; Kadlec, P.; Puerner, F. (Methods of Information in Medicine, 1996)
Data are presented of a controlled experiment with a computerized browsing and encoding tool. Eighteen practicing clinicians extracted medical concepts from two narrative exercise cases using two approaches, traditional and computer-assisted use of ICD-9.Our results indicate that by using a computerized coding tool the completeness of coding can be improved by up to 55%, that by enforcing mandatory as opposed to optional modifier codes results in lower rates of incomplete coding (0 and 55%, respectively), higher rates of correct coding (41 to 92%) and no change in incorrect code, and that manual coding takes twice as long than coding with the help of the computerized coding tool. Clinicians need 59% more time for processing the whole set of codes than is suggested by the sum of individual codes. We conclude that the use of a computerized coding tool can save time and result in higher quality codes. However, the real time spent on coding may be underestimated when looking at individual coding times, instead of the whole task of processing a clinical scenario.
Keywords: Free Text; Coding; ICD-9; Computerized Patient Record; Database Browsing; Encoding Tools; Medical Concepts